Molecular diversity patterns among various phytoplankton size-fractions in West Greenland in late summer. (March 2017) - Elferink, Stephanie; Neuhaus, Stefan; Wohlrab, Sylke; Toebe, Kerstin; Voß, Daniela; Gottschling, Marc; Lundholm, Nina; Krock, Bernd; Koch, Boris P.; Zielinski, Oliver; Cembella, Allan; John, Uwe
Abstract: Arctic regions have experienced pronounced biological and biophysical transformations as a result of global change processes over the last several decades. Current hypotheses propose an elevated impact of those environmental changes on the biodiversity, community composition and metabolic processes of species. The effects on ecosystem function and services, particularly when invasive or toxigenic harmful species become dominant, can be expressed over a wide range of temporal and spatial scales in plankton communities. Our study focused on the comparison of molecular biodiversity of three size-fractions (micro-, nano-, picoplankton) in the coastal pelagic zone of West Greenland and their association with environmental parameters. Molecular diversity was assessed via parallel amplicon sequencing the 28S rRNA hypervariable D1/D2 region. We showed that biodiversity distribution within the area of Uummannaq Fjord, Vaigat Strait and Disko Bay differed markedly within and among size-fractions. In general, we observed a higher diversity within the picoplankton size fraction compared to the nano- and microplankton. In multidimensional scaling analysis, community composition of all three size fractions correlated with cell size, silicate and phosphate, chlorophyll a (chl a ) and dinophysistoxin (DTX). Individually, each size fraction community composition also correlated with other different environmental parameters, i.e. temperature and nitrate. We observed a more homogeneous community of the picoplankton across all stations compared to the larger size classes, despite different prevailing environmental conditions of the sampling areas. This suggests that habitat niche occupation for larger-celled species may lead to higher functional trait plasticity expressed as an enhanced range of phenotypes, whereas smaller organisms may compensate for lower potential plasticity with higher diversity. The presence of recently identified toxigenic harmful algal bloom (HAB) species (such as Alexandrium fundyense and A. ostenfeldii ) in the area points out the potential risk for this vulnerable ecosystem in a changing world. Highlights: Different cell-size phytoplankton is differently affected by abiotic factors. Habitat niche occupation for larger phytoplankton over plasticity is suggested. Smaller organisms may compensate for lower plasticity with higher diversity. Advantage of the small cell-size community in response to environmental conditions is suggested.